(untitled) (Bangladesh Journal of Medical Science, 2013)
Objectives: To outline the spectrum of vertigo, to elaborate the significance of vascular causes of vertigo, to advocate use of MRI / MRA of carotid artery and vetebrobasilar arterial system in patients with isolated or syndromic vertigo especially when one or more risk factors for a cerebrovascular accident are present. Study design: Prospective study(2009-2011). Results: 91 patients who preened with vertigo were prospectively studied. BPPV, Menieres disease and vestibular neuritis comprised about 60% of patients. Posterior circulation syndrome and vertebrobasilar insufficiency was strongly suspected in 13 patients (14.3%). Compression of 8th nerve and cerebellar vermis were documented to be the cause of vertigo in 7 patients (7.7%), cervical vertigo was seen in 6(6.6%) patients. 4 patients (4.4%) had vertigo as a manifestation of complicated CSOM. 3 (3.3%) patients had metabolic vascular syndrome out of which one patient died of stroke about 6 months after his presentation as recurrent episodic vertigo. No diagnosis could be made in 3 patients. Conclusion:A detailed history should be obtained and an elaborate vestibular and neuro-otologic examination done in a patient of vertigo. A diagnosis can be reached in more than 90% of patients. Peripheral vertigo is more common that central vertigo with BPPV, menieres disease and acute vestibular neuritis accounting for more than 60% of all cases of vertigo. Vascular causes form a significant group of vertigo patients. Vertigo especially recurrent and syndromic with 1 or more risk factors should not be overlooked and should be regarded a precursor of a future stroke. Patients of vertigo with vascular risk factors like age (elderly), hypertension, smoking, diabetes mellitus, hyperlipidemia and cardiac disease should be evaluated for vertebrobasilar insufficiency by specific investigations like MRI brain, MRA carotids and vertebrobasilar arteries, Doppler USG and risk factors for vascular disease modified by drugs (hypolipidemic, antihypertensive, aspirin) and behavioural changes. Abnormal vessel loops can compress VIII nerve and cause vertigo. These can be reliably diagnosed by MRA. Vertigo can be caused in patients with cervical spondylosis especially in previously diseased vessels (due to atherosclerosis, vasculitis) which get easily compressed by cervical osteophytes. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 192-198 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14949